2013
DOI: 10.1186/1472-6963-13-290
|View full text |Cite
|
Sign up to set email alerts
|

The provision of and need for social support among adult and pediatric patients with tuberculosis in Lima, Peru: a qualitative study

Abstract: BackgroundTuberculosis (TB) remains a significant public health problem in Peru, causing an estimated 35,000 new cases each year, 6.7% of whom are co-infected with HIV. Social support mechanisms are key in influencing health-seeking behavior, adherence, and overall patient wellbeing in clinical settings. We examine the types of social support received by TB patients and parents of pediatric patients in peri-urban Lima, Peru, to understand its role in patients’ psychosocial wellbeing during treatment.MethodsSem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 24 publications
7
69
1
6
Order By: Relevance
“…In study done by Paz-Soldán et al also reported that parents of child were really selective in disclosing the condition of their children and parents who disclosed the child condition to other family member got tremendous love and care that helped lot in completing the treatment of child. [11] In agreement with other studies, [10][11][12] the suffering experienced by these participants was primarily linked to the likelihood of being discriminated against, which made them feel stigmatized. Despite TB being a curable disease, many professionals' different streams such as psychologists, anthropologists, sociologists, and TB analysts have repeatedly indicated that talking about the disease still causes discomfort and unease.…”
Section: International Journal Of Medical Science and Public Healthsupporting
confidence: 78%
See 2 more Smart Citations
“…In study done by Paz-Soldán et al also reported that parents of child were really selective in disclosing the condition of their children and parents who disclosed the child condition to other family member got tremendous love and care that helped lot in completing the treatment of child. [11] In agreement with other studies, [10][11][12] the suffering experienced by these participants was primarily linked to the likelihood of being discriminated against, which made them feel stigmatized. Despite TB being a curable disease, many professionals' different streams such as psychologists, anthropologists, sociologists, and TB analysts have repeatedly indicated that talking about the disease still causes discomfort and unease.…”
Section: International Journal Of Medical Science and Public Healthsupporting
confidence: 78%
“…[11] The present study noted participants thinks that coming to here at health center and taking drugs in the presence of DOTS provider helped them in reminding to take regular treatment and if they forgot or have any problem during the course of treatment, there is someone who can help them. In case of home-based DOTS strategy that would be a question mark as many times child do not want to take drugs and it is hard for mother to convince them compared to taking drugs in the presence of DOTS provider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos estudios cualitativos realizados en poblaciones vulnerables, en riesgo o en grupos excluidos en el Perú y en países en vías de desarrollo, se han realizado utilizando diversas técnicas como grupos focales, observaciones y entrevistas a profundidad (2)(3)(4) …”
Section: Los Factores Socioculturales En El Marco De Sistemas De Infounclassified
“…que explora e identifica los aspectos socioculturales en pacientes con tuberculosis en el Perú, como la necesidad de tener soporte social (rol de la familia y del personal de salud), el valor del soporte emocional, el estigma percibido por los pacientes con tuberculosis, el rol de las redes sociales, entre otros (2) .…”
Section: Referencias Bibliográficasunclassified